Study of the Usability of an Augmented Reality Application in the Basic Construction of a Robotic Arm - Malpartida Valverde, Jose (2022)
Augmented reality (AR) can help in different areas of scientific research, such as handling expensive, easy-to-break or dangerous equipment. Since the components for the construction of a robot can be considerably expensive, augmented reality can be applied in the manufacture of robots to reduce costs, allowing users to experience handling robotic components without having to buy them. This study aims to measure the quality of user experience with an augmented reality application in robotics. To do this, we created an application that uses hand gestures to assemble a robotic arm. This article presents the results obtained, the user’s efficiency rates in assembling the robotic arm, and an assessment of the application’s usability. The study aims to measure the quality of the user experience when interacting with an AR application in the field of robotics. Therefore, the application was built that uses hand gestures to instantiate the links as 3D images and subsequently assemble their mechanical parts of the robotic arm. Favorable results obtained are presented, such as the efficiency of users in assembling the links of the robotic arm, as well as the usability of the application in the conclusions.